1991
DOI: 10.1007/bf00114599
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of degradative enzymes in white-rot decay of lignocellulose

Abstract: The use of immunogold-cytochemical labelling techniques in electron microscopy of wood infected by basidiomycete fungi has assisted in the elucidation of the localisation of enzymes which degrade lignocellulose. The use of specific immunocytochemical techniques is discussed with respect to the authenticity and accuracy of the methods, the use of adequate controls in the gold-labelling procedure, and the immunospecificity of the antibodies.Localisation of the lignin-degrading enzymes, lignin-peroxidase and lacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…A synergistic effect has been observed between adsorption and subsequent biodegradation, caused by the extracellular ligninolytic system (Palma, 1998). This process is probably associated to the previous adsorption process by the mycelium as this permits a close contact between the chromophore group and the degrading enzymes which are associated to the surface of the hyphae (Evans et al, 1991;Yang et al, 2003). Figure 1b shows that in the batch culture with an alternative substrate there is an increment with respect to the control culture, both in biomass and in activity level.…”
Section: Static Culturementioning
confidence: 99%
“…A synergistic effect has been observed between adsorption and subsequent biodegradation, caused by the extracellular ligninolytic system (Palma, 1998). This process is probably associated to the previous adsorption process by the mycelium as this permits a close contact between the chromophore group and the degrading enzymes which are associated to the surface of the hyphae (Evans et al, 1991;Yang et al, 2003). Figure 1b shows that in the batch culture with an alternative substrate there is an increment with respect to the control culture, both in biomass and in activity level.…”
Section: Static Culturementioning
confidence: 99%
“…Enzyme localization with electron* microscopic study of infected wood has shown that lignocellulolytic enzymes cannot penetrate into the wood structure except where the wood cell wall is already partially decayed (Evans et al 1991;Flournoy et al 1991Flournoy et al , 1993. Therefore the initiators of both cellulose and lignin breakdown are most probably low molecular weight molecules that can readily diffuse away from the hyphae and penetrate through the pores into the lignocellulosic matrix of the cell wall.…”
Section: Introductionmentioning
confidence: 98%
“…1987;Ruel et aL 1989;Srebotnik et al 1988). Recently Evans et aL (1991) postulated that none of the enzymes currently identified as being involved in the degradation of lignin or cellulose initiate the process of decay as none were localized to any significant extent in the undecayed wall and middle lamella.…”
Section: Resultsmentioning
confidence: 98%
“…Although considerable research, including the isolation and study of lignin degrading enzymes from white rot fungi (Glenn and Gold 1985;Tien and Kirk 1983) was conducted, additional study is necessary to understand the mechanism by which these fungi and their metabolites act to degrade lignin in situ. Immuno-TEM procedures have been recently used to localize the extracellular metabolites of wood decay fungi both within the fungal hyphae and in the wood cell wall (Blanchette et al 1989;Daniel et al 1989;Evans et al 1991;Garcia et al 1988;Goodell et al 1988;Kim et al 1991a;Srebotnik et al 1988;Srebotnik and Messner 1991). The purpose of the following investigation was to visualize via iminuno-TEM techniques the extracellular metabolites from Trametes versicolor using polyclonal antiserum raised against this white-rot fungus.…”
Section: Introductionmentioning
confidence: 98%